Atomic mechanisms of local structural rearrangements in strained crystalline titanium grain; Technical Physics Letters; Vol. 37, iss. 10 - Konovalenko I. S. Ivan Sergeevich; Kryzhevich D. S.; Zol'nikov K. P.; Psakhie S. G. Sergey Grigorievich (2011, 2011)
Title screen